Synthesis of green anode material for lithium-ion battery from orthodontic waste by fuzzy logic - Ashraf, Humza; Karahan, Billur Deniz; Şen, Zekai (My University, 2025)
For the fabrication of green batteries, instead of synthesizing the electrode materials from high-purity metal powders via primary production methods, it is of great importance to design and produce an electrode material by recovering valuable elements from existing wastes. In this article, for the first time in open literature, an electrode active material was fabricated from biomedical waste by using a combination of leaching and hydrothermal methods. Once 100% leaching efficiency was achieved, an optimization was realized in the hydrothermal parameters (filling ratios, time, and temperatures) to fabricate spherically shaped metal oxide powders with 150 nm particle size. Innovatively, fuzzy logic modeling was used for refinement of parameters. Subsequently, three verification experiments were realized at optimum conditions, defined by fuzzy logic. The repeatability as well as the accuracy of the model was confirmed. In the meantime, analysis of variance (ANOVA) technique was applied for identification of the most effective parameter for the fabrication of powders in hydrothermal conditions. A detailed mechanistic analysis about the formation of particles was also realized. Finally, the possible use of this metal oxide powder as an anode material was evaluated galvanostatically and potentiostatically. The electrode delivered a higher capacity than graphite and achieved 100-cycle tests with success. The presented approach was anticipated to constitute an example for the future, as it brought an effective perspective to material scientists about the valorization of biomedical waste in high value-added applications such as energy storage devices.
Keywords: Fuzzy Logic; Nanocomposite; Orthodontic Waste Valorization; Transition Metal Oxide Anode; Waste To Source